Artificial Intelligence - Pratt, Ian (Computer Science Series, 1994)
While assuming no prior knowledge of AI or logic, this book provides a clear and readable introduction to many of the most advanced developments in AI, as well as giving examples of their usage and critically assessing their applicability and effectiveness. Topics covered include planning, logic and inference, non-monotonic logic, reason maintenance, memory organization, probabilistic reasoning, induction and neural networks. By concentrating on inference as a central theme, the author is able to present material more sophisticated than that covered by other university textbooks in the subject. The book will therefore be particularly suitable for advanced undergraduate and graduate courses in AI.